Dr. Juan Hernando Santamaría — Deep Plane Facelift — Medellín - Santamaría, Juan Hernando (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Juan Hernando Santamaría, practicing in Medellín, Colombia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003340; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; colombia; medellín